Determinants of Pro-environmental Behaviours – A Cross Country Study of Would-be Managers - Asit Bhattacharyya; Kumar Biswas; Abdul Moyeen (Australasian Accounting, Business and Finance Journal, 2020)
Purpose: This cross-cultural based paper aims to provide an understanding of the determinants contributing to adopting pro-environmental behaviour by ‘would-be managers’ represented by MBA students studying in two highly carbon emitting yet contrasting countries – India and Australia. The paper particularly examines the effects of personal values, moral obligation, attitudes, and subjective norms on pro-environmental behavior of such would-be managers. Design/methodology/approach: In predicting the pro-environmental behavior of would-be managers, a conceptual model was developed by combining Schwartz’s (1992) value theory and Homer and Kahle’s cognitive hierarchy model of value-attitude-behaviour (VAB). Data was collected from 476 respondents consisting of 342 MBA students from India and 134 MBA students from Australia. Partial least square based structural equation modeling (PLS-SEM) was used in analysing the data. Findings: The findings reveal that the inclination of pro-environmental behaviour of would-be managers can be predicted by their personal value, moral obligation, attitudes and subjective norms, thereby providing both theoretical and empirical supports to our model in understanding the determinants of pro-environmental behaviour. Practical implications: The findings are critical in developing strategies for building capacity and willingness of would-be managers to adopt pro-environmental behaviour. In so doing, business schools may use these findings in designing effective CSR/sustainable development contents in their curriculum which will not only help educators to nurture classroom discussion but also sensitize students’ critical thinking in addressing issues of climate change as well as improving environmental well-being. Originality/value: Conceptually, this paper proposes a comprehensive framework to understand the determinants of pro-environmental behavior. Empirically, it applies a novel and appropriate method for predicting such behavior in two contrasting yet highly carbon emitting countries – an important issue that receives little attention in current CSR/sustainable development literature.
Keywords: Pro-environmental behaviour; Would-be managers; India; Australia; Cross-cultural study.